Alat Optimasi Suhu dan Kelembaban untuk Inkubasi Fermentasi dan Pengeringan Pasca Fermentasi - Gunawan Dewantoro; Sri Hartini; Agustinus Hery Waluyo (Jurnal Rekayasa Elektrika, 2015)
Fermentation optimizer aids have been common around us in both laboratories and home industries. However, these aids only served as incubator and sometimes cannot optimize the fermentation process due to the increasing humidity in a closed box. Nevertheless, adding holes to the box will not lead to a better result since unwanted bacterias come into the box. Therefore, a fermentation optimizer aids has been realized with two separate functions, namely fermentation incubator and post-fermentation dryer. This kit works in the temperature ranging from 35 degree C – 120 degree C, and equipped with two exhaust fans to minimize the humidity in both fermentation and dryermodes. The SHT11 was utilized to measure the temperature and relative humidity. A ceramic heater was used to warm up the air inside the box as desired by users. As the user interface, keypad and character LCD were used. ArduinoMega2560 serves as the main controller of the whole system. Compared to the conventional fermentation process, this kit works 9 hours faster and the fermentation objects are perfectly fermented.